Investigation and evaluation of surface water pollution with heavy metals and oil products in Kairiai military ground territory - Idzelis, Raimondas Leopoldas; Greičiūtė, Kristina; Paliulis, Dainius (Journal of Environmental Engineering and Landscape Management, 2006)
Water pollution with heavy metals, oil and its products is a very important environmental problem. Major part of chemical elements penetrating into the environment gets accumulated in the soil and bed sediment of water bodies. They may also migrate into surface, ground and underground water and spread at great distances. From here, they may enter again nutritional chains and poison living organisms. It is very important and necessary to investigate military territories and evaluate their environmental condition in order to identify the works of their cleaning and optimization of their environmental condition as well as their scope. However, not all the military territories in Lithuania have been sufficiently investigated so far, damage to the environment is not known. Therefore, investigation of such territories is of utmost importance, it is of scientific and environmental significance. This work is dedicated to the investigation and evaluation of surface water and bed sediment pollution with heavy metals and oil products in one of the biggest military grounds of Lithuania ‐ Kairiai Military Ground. Results of the investigation allowed answering the main questions about the most common pollutants, spreading in the environment because of military activities, to determine the level of pollution and most vulnerable territories. Vandens telkinių užtaršos sunkiaisiais metalais ir naftos produktais Kairių kariniame poligone tyrimai ir vertinimas Santrauka. Paviršinio vandens bei jo telkinių dugno nuosėdų tarša sunkiaisiais metalais, nafta ir jos produktais – svarbi aplinkosaugos problema. Teršalai gali sklisti į aplinką garuodami ar migruodami gilyn ir užteršdami gruntinius vandenis. Nors yra žinoma, kad vienas iš karinės veiklos padarinių yra labai užteršti grunto plotai bei vanduo, tačiau vis dar stinga konkrečių duomenų apie tam tikrų teritorijų ruožų užterštumo lygį. Dar nėra pakankamai surinkta faktinės medžiagos apie karinių poligonų teritorijose daromą žalą įvairiems aplinkos komponentams. Šiame darbe įvertinta Kairių karinio poligono vandens telkinių užtarša sunkiaisiais metalais bei naftos produktais. Tyrimams parinktos būdingos vandens telkinių užtaršos vietos viename iš didžiausių – Kairių kariniame poligone. Tyrimo metu nustatyta Kairių poligono teritorijoje esančių paviršinio vandens telkinių ir jų dugno nuosėdų užtarša sunkiaisiais metalais bei vandens užtarša naftos produktais. Tyrimas leido atsakyti į esminius klausimus: kokie teršalai būdingi karinei veiklai naudojamiems vandens telkiniams, kokie yra užterštumo lygiai bei kurios vietos taršai jautriausios. Reikšminiai žodžiai: kariniai poligonai, paviršinio vandens telkiniai, tarša, sunkieji metalai, naftos produktai, dugno nuosėdos. Исследование и оценка загрязненности вод водоемов тяжелыми металлами и нефтепродуктами на территории военного полигона в Кайряй Резюме. Загрязненность вод и осадков дна тяжелыми металлами, нефтью и ее продуктами – важная экологическая проблема. Загрязняющие вещества могут попасть в окружающую среду с выделяющимися из них газами или еще хуже – всасываются в почву, загрязняют грунтовые воды и таким образом могут попасть на территории, находящиеся далеко от источника загрязнения. Хотя уже давно известно, что одним из последствий военных действий являются сильно загрязненные поверхностные воды и почва, все еще не хватает конкретных данных об уровне загрязнения отдельных участков. Еще не собрано достаточно фактической информации о негативных факторах, которые испытывают отдельные компоненты окружающей среды на территориях военных полигонов. В статье представлено исследование, которым была установлена загрязненность поверхностных вод на территории полигона в Кайряй тяжелыми металлами и нефтепродуктами, а также осадков дна тяжелыми металлами. Для исследования были подобраны типичные места на одном из самых больших полигонов Литвы – в Кайряй. Результаты исследования помогли ответить на вопрос о том, какие загрязняющие вещества в поверхностных водах, используемых для военных действий, встречаются чаще всего, какой степени достигло загрязнение, и т. п. Ключевые слова: военные полигоны, поверхностные воды, загрязненность, тяжелые металлы, нефтепродукты, осадки дна. Firstd Published Online: 14 Oct 2010